Transcriptomic analysis of human non-small lung cancer cells A549 treated by one synthetic curcumin derivative MHMD - Zhou, G.; Sun, G.; Zhou, Y.; Wang, Q. (Cellular and Molecular Biology, 2017)
In our previous studies, we have identified one curcumin analog MHMD could induce apoptosis of lung cancer cells A549 via extrinsic and intrinsic pathways in our previous studies. But the specific regulatory genes and molecular mechanisms remain poorly understood. Here, the transcriptomic profile of A549 cells was detected with RNA-seq technique after MHMD treatment at 48 h. A total of 16584651 clean data from 21831774 sequence reads were obtained and 80.75% of them could be mapped on the human test genome. 18635 unigenes with the mean length of 4027 bp were finally assembled. 850 up-regulated and 855 down-regulated genes were differently expressed in MHMD-incubated A549 cells, which were involved in many cellular pathways of MHMD-treated A549 cells. Furthermore, the major genes involved in the apoptotic and NSCLC pathways were analyzed. mRNAs of four genes (casp7, p53, tgfa, prkar1b) were validated by RT-PCR, which suggested that MHMD indeed activated the apoptotic pathway of A549 cells.